INVESTIGATION OF CORROSION STEEL IN THE CARBON DIOXIDE ENVIRONMENT - Niyazbekova, A. B.; Zhaskairatova, Zhaskairatova (Ғылым және білім №3, 2020)
Corrosion of steel equipment of wells, as well as main and process pipelines, in addition to reducing their exploitation and increasing their repair costs, can cause serious damage to the environment. Damage to equipment leads to salinization of soils with aggressive reservoir water, contamination of soils and natural reservoirs with oil and oil products. In oil fields, much attention is paid to the problem of extending the service life of well processing equipment. One of the most effective ways to protect field equipment and pipelines from corrosion in the oil and gas industry is the use of corrosion inhibitors. Inhibitor protection is the most common and economically justified method of anticorrosion protection of field equipment and pipelines. By changing the dosage of the inhibitor or using inhibitors with different anti-corrosion properties, it is possible to reduce the corrosion rate to an acceptable level without fundamentally changing the existing technological schemes. Oil and gas companies have high requirements for inhibitory compositions, requiring them to have universal action.Коррозия стального оборудования скважин, а также магистральных и технологических трубопроводов, помимо уменьшения срока их эксплуатации и увеличения затрат на их ремонт, может нанести серьезный ущерб окружающей среде. Повреждение оборудования приводит к засолению почв агрессивной пластовой водой, загрязнению почв и природных водоемов нефтью и нефтепродуктами. В данной статье приведен анализ литературных источников по исследованиям коррозии стали в углекислой среде, приведены механизмы углекислотной коррозии стали, а также проведен анализ известных ингибиторов и охарактеризовано их влияние к углекислотной коррозии стали. Приведенный анализ литературных источников показывает, что, несмотря на широчайший ассортимент ингибиторов коррозии отечественного и зарубежного производства, представленных на рынке, проблема защиты металлического оборудования газо- и нефтепромыслов от углекислотной коррозии продолжает оставаться актуальной и на сегодняшний день наиболее перспективным является создание ингибиторов универсального действия, обладающих достаточным защитным эффектом в условиях сероводородной и углекислотной коррозии.
Keywords: рк; научный журнал; периодическое издание; отечественное издание; коррозия оборудования скважин; коррозия стали; ингибиторы; metal corrosion; inhibitors; carbon dioxide environment; gas field